Consultation and cultural heritage : Let us reason together - Nissley, Claudia; King, Thomas F. (Left Coast Press, 2014)
This pragmatic guide to consultation in cultural heritage and environmental impact management distills decades of experience by two of the leading figures in this area. Claudia Nissley and Tom King reject the idea that consulting with communities and other stakeholders is merely checking off a box on the list of tasks required to implement a project. Instead, they show government agencies and project sponsors how to find the relevant parties, to discuss the project in an open and continuous fashion, to consider alternative strategies, and to seek agreement that meets everyone's needs. The.